Interpretasi Kritisisme Immanuel Kant dalam Budaya Jawa Modern - Benny Baskara (Jurnal Filsafat "WISDOM", 2003)
This essay purposed to make interpretation about critisism, in this case critical thinking process on Modern Javanese Culture. Critical thinking actually can reveral the ancient and traditional Javanese values into reasonable and scientific explanations. This process create many advantages for the development of Javanese Culture, especially the change from traditional to modern. Javanese people start with modern lifestyle which critical thinking as "the main thinking way" on each day life. That also proved for Javanese modern is free from "dogmatism trap" of traditional thinking process.On the other side, modern life also make its own "new dogmatism". Many people never realize, within their life begin to fall into meaningless and deceived world. Javanese modern people just threated radically pull out from their own culture values, that believed for many years and generations before. The honesty of Javanese even hard questioned in the modern life, that shows the degradation of ethic values belief. This indicate modern people do not have a "pure practical reason" as fundamental reason for daily activities.